Evidence of Pulmonary Hypertension after SARS-CoV-2 Infection in Subjects without Previous Significant Cardiovascular Pathology - Tudoran, Cristina; Tudoran, Mariana; Lazureanu, Voichita Elena; Marinescu, Adelina Raluca; Pop, Gheorghe Nicusor; Pescariu, Alexandru Silvius; Enache, Alexandra; Cut, Talida Georgiana (Journal of clinical medicine, 2021)
Background: Coronavirus (Covid-19) infection represents a serious medical condition, often associated with cardiovascular complications, pulmonary hypertension (PH), and right ventricle dysfunction (RVD). The aim of this study is to show, by means of transthoracic echocardiography (TTE), the presence of an increased estimated systolic pressure in the pulmonary artery (esPAP) and altered right ventricular global longitudinal strain (RV-GLS) in patients without history of PH. Methods: In a group of 91 patients, aged under 55 years, hospitalized for a moderate Covid-19 infection, a thorough cardiologic and TTE examination were performed two months after discharge. Their initial thorax computer-tomography (TCT) images and laboratory data were accessed from the electronic data base of the hospital. Results: We observed an increased prevalence of PH (7.69%) and RVD (10.28%), significantly correlated with the initial levels of the TCT score and inflammatory factors (p ˂ 0.001), but borderline changes were observed in more patients. Multivariate regression analysis showed that these factors and RV-GLS explain 89.5% of elevated esPAP. Conclusions: In COVID-19 infection, PH and RVD are common complications, being encountered after the recovery even in moderate cases. It appears to be a connection between their severity and the extent of the initial pulmonary injury and of the inflammatory response.